The Attributes of Sacredness of Animals on the Reliefsof Armenia and Georgia (6th-14th Centuries) - Mikayelyan, Lilit (Институт языкознания РАН)
In Armenian and Georgian sculpture of the 6th-14th centuries, there are many images of real and fantastic animals with certain attributes: ribbons, necklaces, wreaths, crowns. One of the oldest examples of such iconography is known on the 8th-6th century BC Urartian statuette depicting a crowned sphinx with a ribbon tied to its torso. The use of ribbons and necklaces as attributes of animal sacredness becomes especially popular in the culture of Sasanian Iran of the 5th-7th centuries, where they indicated the royal, benevolent symbolism of the images. Bird figures with ribbons around their necks in Armenian, Georgian, and East Christian art of the 5th-7th centuries reveal the obvious influence of Sasanian iconography. In Christian art, these attributes denoted the victorious, heavenly symbolism of images. In the 10th-14th centuries, a number of fantastic animals: griffins, sirens, sphinxes are usually depicted with necklaces and crowns – as markers of their belonging to the upper world. В армянской и грузинской скульптуре VI-XIV веков известно множество изображений реальных и фантастических животных с определенными атрибутами: лентами, ожерельями, венцами, коронами. Один из древнейших примеров такой иконографии известен на урартской статуэтке VIII-VI веков до н.э., изображающей коронованного сфинкса с лентой на туловище. Использование лент и ожерелий как атрибутов сакральности животных становится особенно популярным в культуре Сасанидского Ирана V-VII веков, где они указывали на царственную, благопожелательную символику образа. Изображения птиц с лентами на шеях в армянском, грузинском, а также восточнохристианском искусстве V-VII веков показывают очевидное влияние сасанидской иконографии. В христианом искусстве эти атрибуты указывали на победную, небесную символику образов. В X-XIV веках ряд фантастических животных: грифоны, сирены, сфинксы как правило изображались с ожерельями и коронами – маркерами их принадлежности верхнему миру.
Keywords: Arts